Incidental Diagnosis Of Huge Arachnoid Cyst Causing Macrocrania: A Case Report - Ak, Hakan; Aydın, Varol; Samancıoğlu, Halil (Fırat University, 2012)
Arachnoid cysts are the benign developmental malformations of arachnoid compromising of about 1 % of all intracranial space occupying lesions. It was reported that trauma, also, might play a role in the pathogenesis of these lesions. These cysts are frequently seen in early childhood and have a tendency to middle fossa. These cysts frequently present with headache, dizziness, or epilepsy and suboptimal cerebral function like disordered perception. Natural course and treatment of these cysts are still in debate. In this report, we are presenting a 10 month year old child having symptomatic huge arachnoid cysts in middle fossa determined incidentally after trauma. In the treatment of this case, cystoperitoneal shunt operation was performed and good result was gained even in the early postoperative period. However, the main topic of this report is to emphasize that sometimes symptomatic cases might be overlooked.

İntrakranyal yer kaplayan oluşumların %1'ini oluşturan araknoid kistler araknoid membranın iyi huylu gelişimsel malformasyonudurlar. Travmanın da patogenez de rol oynayabileceği bildirilmiştir. Bu kistler erken çocukluk döneminde ve orta fossada daha sık görülmektedir. Sıklıkla baş ağrısı, baş dönmesi veya epilepsi ve bozulmuş algılama gibi suboptimal serebral fonksiyonla ilişkili spesifik olmayan semptomlar oluştururlar. Bu lezyonların doğal seyirleri ve tedavileri ile ilgili olarak tartışmalar halen sürmektedir. Bu yazıda aslında semptom oluşturmuş olmasına rağmen travma sonrası tesadüfen tespit edilmiş dev araknoid kist ile başvuran bir olgu sunulmaktadır. Olguya kistoperitoneal şant takılmış ve erken dönemde iyi sonuç alınmıştır. Ancak bu yazıda asıl vurgulanmak istenen ana düşünce semptomatik olguların bazen gözden kaçabilmesidir.
Makrokraniya Oluşturmuş Dev Araknoid Kistin Rastlantısal Tanısı: Olgu Sunumu